Podcasting Feminism: The Multimodality of Women’s Writing and Literary-Historical Studies - Hurrell, Christie; Holland, Kathryn; Bourrier, Karen; Khuu, Jessica (KULA)

(untitled) (University of Victoria Libraries, 2025)
Created by a team of literary scholars, students, and a librarian, Orlando: A Podcast on Womenʼs Writing comprises twelve informal interviews that synthesize and share scholarly work on womenʼs writing from medieval times to the present, with capacious definitions of “women” and “writing.” The podcast is closely connected to Orlando: Womenʼs Writing in the British Isles, from the Beginnings to the Present (Cambridge UP, 2006–), a textbase of original scholarship on womenʼs writing encoded with a bespoke XML tagset. Examining the interplay between the podcast and textbase within our broader scholarly landscape, this audio essay focuses on issues inherent in translating knowledge between written and oral forms in the podcast lifecycle, from the process of creating a lively and accessible scholarly interview to the difficulties of transcription. This discussion mirrors the content of the podcast: feminist critics like Diane Watt, whom we interview about medieval writer Margaret Paston, have challenged the idea that women needed to read the written word in order to be considered literate, arguing that dictation could constitute an alternative form of literacy. By challenging text-based representation as the primary legitimate form of scholarship, we foster a more inclusive view of scholarly communication that speaks to the existing tradition of multimodality in feminist writing. Providing insight on the affordances of the podcast medium and library partnerships for advancing the aims of feminist scholarship and the preservation of new forms of scholarship, the essay explores our reflections on networked knowledge production and multimodal representation, which make scholarship accessible in and beyond academic contexts.